2018
DOI: 10.1111/bdi.12652
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive probiotic microorganisms to prevent rehospitalization in patients with acute mania: A randomized controlled trial

Abstract: Probiotic supplementation is associated with a lower rate of rehospitalization in patients who have been recently discharged following hospitalization for mania.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 41 publications
4
78
0
Order By: Relevance
“…Moreover, the same research group further reported that 3‐month supplement with this probiotic formula could improve of performance concerning attention, psychomotor processing speed, and executive function in euthymic patients with BD 78 . Another study suggested that adjunctive probiotic supplement ( Lactobacillus GG strain and Bifidobacterium lactis strain) reduced the rehospitalization rate in patients who were recently discharged for mania 79 . Although the exact mechanisms by which probiotic microorganisms benefit for mental health remain unknown, it is possible that they reconstruct the gut microbiota and modulate host immune reactions in response to various antigens 75 .…”
Section: Future Directionsmentioning
confidence: 99%
“…Moreover, the same research group further reported that 3‐month supplement with this probiotic formula could improve of performance concerning attention, psychomotor processing speed, and executive function in euthymic patients with BD 78 . Another study suggested that adjunctive probiotic supplement ( Lactobacillus GG strain and Bifidobacterium lactis strain) reduced the rehospitalization rate in patients who were recently discharged for mania 79 . Although the exact mechanisms by which probiotic microorganisms benefit for mental health remain unknown, it is possible that they reconstruct the gut microbiota and modulate host immune reactions in response to various antigens 75 .…”
Section: Future Directionsmentioning
confidence: 99%
“…Thus, we cannot determine whether observed microbial changes are due to treatment or other potential sources of bias. Earlier randomized, double-blinded, placebo-controlled trials investigating probiotic interventions in SMI have reported to improve bowel function (Dickerson et al, 2014), reduce levels of intestinal inflammatory indices (Severance et al, 2017), and increase levels of systemic immunomodulatory proteins (Tomasik et al, 2015), but the findings with regards to psychiatric outcomes are still mixed (Dickerson et al, 2018(Dickerson et al, , 2014Severance et al, 2017). These studies did not assess microbial biomarkers pre-or post-treatment, so the relationship of the immune and clinical responses to gut microbial composition remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The Lactobacillus casei and Bifidobacteria groups are some of the most widely researched and applied probiotic species (Hill et al, ). The health‐promoting capabilities of these probiotics have been documented in child asthma (Kalliomaki et al, ), mania (Dickerson et al, ), and obesity (Luoto, Kalliomaki, Laitinen, & Isolauri, ). Previous research has shown that administration of Lactobacillus acidophilus in the gut results in analgesic effects in rodents similar to those observed with morphine (Rousseaux et al, ) and that the Escherichia coli strain Nissle 1917 provided analgesia for the visceral pain associated with irritable bowel syndrome (Perez‐Berezo et al, ).…”
Section: Discussionmentioning
confidence: 99%